The rhetorical analysis of the Letter to the Galatians: 1995-2005 - D. F. Tolmie (Acta Theologica)
Since the publication of Betz’s article (1975) and his commentary on Galatians (1979) much research has been done on the rhetorical analysis of the Letter to the Galatians. This article presents an overview of the rhetorical analyses of Galatians from 1995 to 2005. It concludes by highlighting five characteristics of such analyses: 1. The rigid application of “the” ancient rhetorical system is on the decline; 2. Scholars who still use insights from ancient rhetoric do so in a much more nuanced way, quite often presuppose a wider background, and are more interested in functions than in categories; 3. There has been a notable increase in the use of rhetorical approaches that were not based on ancient rhetoric; 4. The fact that Galatians is a letter has received more serious consideration; 5. A new issue that has been raised is the applicability of an “evaluative” approach to Paul’s argumentation and persuasive strategy.